Characterisation of gas-liquid two-phase flow in minichannels with co-flowing fluid injection inside the channel, part I: unified mapping of flow regimes. (December 2016) - Haase, Stefan
Highlights: Gas–liquid downflow was studied experimentally at a pressure of 1 MPa. Capillary injectors of different diameters were used as gas-liquid feeding system. Homogeneous Taylor flows were created for a broad range of phase velocities and holdups. Three different bubble-forming mechanisms were found. Criteria for regime transition based on dimensionless numbers are provided. Abstract: Present research highlights the potential of apparatuses with integrated minichannel packings to intensify gas-liquid-solid contacting. Especially an operation of these devices within the Taylor flow regime gained extraordinary attention due to its excellent heat and mass transfer and the segmented flow characteristics. However, criteria for flow regime transitions are mainly developed from water-similar fluids and are contradictory which hinders uniform flow regime prediction. This work presents a systematic analysis of adiabatic gas-liquid downflow in a square minichannel of 1.0 mm hydraulic diameter. In the mixing zone located within the flow channel, gas was injected into the co-flowing liquid by so-called capillary injectors with variable inner diameter (0.184, 0.317, 0.490 mm). Experiments were conducted using water, water-glycerol, and water-ethanol mixtures to cover a broad range of material properties. The gas and liquid superficial velocities were varied between 9.81·10 -4 …2.72 m/s and 1.7·10 −4 …0.80 m/s, respectively. Taylor flow, Taylor-annular flow, annular flow, churn flow, and bubbly flow were observed. Using the Pi-theorem, 8 significant dimensionless groups dictating the flow transition were identified, namely u G, s / u L, s, ReG, ReL, WeG, WeL, Θ *, d In, CI / dh, and d Ou, CI / dh . Based on more than 1500 experimental data, criteria for the regime transitions of Taylor flow are provided. The derived flow regime map shows good agreement for all applied liquids and for the two larger injector geometries. Graphical abstract: